2016
DOI: 10.4309/jgi.2016.33.2
|View full text |Cite
|
Sign up to set email alerts
|

Parent problem gambling: A systematic review of prevention programs for children

Abstract: Parent problem gambling (PG) has pervasive adverse effects on children. These children experience considerable losses such as loss of trust, loss of safety and stability, as well as financial and emotional losses. They are at greater risk for maltreatment and mental health disorders, and they are also at risk for intergenerational transmission of PG. These children are two to four times more likely to develop PG than children of non-PG parents. To date, there has been a dearth of research examining the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Although gambling is often conceptualized as an adult activity, research has consistently shown that problem gambling is an emergent public health issue among adolescents and emerging adults (Calado et al 2017a), and is part of a broader constellation of other risk behaviours (antisocial, risk-taking, delinquent behaviours) at this developmental stageparticularly for males. Youth problem gambling can bring about severe negative consequences both in the short-term and in the long-term, such as mental health concerns (e.g., mood disorders, anxiety disorders), and behavioural problems (e.g., Kourgiantakis et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although gambling is often conceptualized as an adult activity, research has consistently shown that problem gambling is an emergent public health issue among adolescents and emerging adults (Calado et al 2017a), and is part of a broader constellation of other risk behaviours (antisocial, risk-taking, delinquent behaviours) at this developmental stageparticularly for males. Youth problem gambling can bring about severe negative consequences both in the short-term and in the long-term, such as mental health concerns (e.g., mood disorders, anxiety disorders), and behavioural problems (e.g., Kourgiantakis et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of prevention frameworks, the literature has identified three types of prevention initiatives for this particular problem: primary, secondary and tertiary (see Kourgiantakis et al 2016). The former includes activities targeted to youth populations who not gamble to prevent gambling problems from arising in the first place, with the goal of increasing awareness of the risks involved and consequences associated with problem gambling behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Follow up evaluations on actual PG behaviour should be conducted to investigate long-term effects of prevention programs, as youths who are exposed to gambling at a young age could potentially develop PG during adulthood (Kourgiantakis et al 2016). This indicated that PG can develop throughout youths’ developmental life span, highlighting the need for programs with sustained long-term effect on actual PG outcomes and mental health.…”
Section: Discussionmentioning
confidence: 99%